Comparison of GFR measurement with [99mTc]-DTPA and clinical methods based on creatinine measurement, in patients over 80 years old - Claudio, Maioli; Michela, Mangano; Luca, Tagliabue (Journal of Clinical Nephrology, 2022)
Introduction and aim: The most accurate way of measuring kidney function in GFR. Clinical formulas based on creatinine measurement may be inaccurate mainly in elderly patients (over 80 years of age). In this study we evaluated the accuracy of commonly used clinical formulas by comparing them with a direct measurement with [99mTc]-DTPA ([99mTc]-diethylene-triamine-peracetic acid) in a population of patients aged eighty and older. Material and methods: 47 patients (27 males and 20 females) with an average age of 81.9 ± 1.7 years, 80% already diagnosed with Chronic Kidney Disease (CKD), were investigated. Two plasma samples were collected between 60-90 and 165-190 minutes after the injection of [99mTc]-DTPA and GFR were calculated. Results: When comparing the GFR values obtained from the various formulae by creatinine levels with the GFR value obtained by measuring [99mTc]-DTPA residue, the following concordance values emerged: (1) MDRD: 55.3%, (2) Cockroft-Gault 55.3% (3) CKD-EPI 57.5% (4) BIS-1 51.1%. Conclusion: Our data show a poor correlation between all clinical methods and [99mTc]-DTPA, which remains a gold standard for the direct measurement of GFR.